Deregulated gene expression pathways in myelodysplastic syndrome hematopoietic stem cells. - Pellagatti, A; Cazzola, M; Giagounidis, A; Perry, J; Malcovati, L; Della Porta, MG; Jädersten, M; Killick, S; Verma, A; Norbury, C; Hellström-Lindberg, E; Wainscoat, J; et al. (2010)
To gain insight into the molecular pathogenesis of the myelodysplastic syndromes (MDS), we performed global gene expression profiling and pathway analysis on the hematopoietic stem cells (HSC) of 183 MDS patients as compared with the HSC of 17 healthy controls. The most significantly deregulated pathways in MDS include interferon signaling, thrombopoietin signaling and the Wnt pathways. Among the most significantly deregulated gene pathways in early MDS are immunodeficiency, apoptosis and chemokine signaling, whereas advanced MDS is characterized by deregulation of DNA damage response and checkpoint pathways. We have identified distinct gene expression profiles and deregulated gene pathways in patients with del(5q), trisomy 8 or -7/del(7q). Patients with trisomy 8 are characterized by deregulation of pathways involved in the immune response, patients with -7/del(7q) by pathways involved in cell survival, whereas patients with del(5q) show deregulation of integrin signaling and cell cycle regulation pathways. This is the first study to determine deregulated gene pathways and ontology groups in the HSC of a large group of MDS patients. The deregulated pathways identified are likely to be critical to the MDS HSC phenotype and give new insights into the molecular pathogenesis of this disorder, thereby providing new targets for therapeutic intervention.